Sosialisasi Tentang Penigkatan Kesadaran Masyaraka Terkait Hak-Hak Perempuan dalam Partisipasi Pembagunan Desa.: Gender - Bere, Maria Istaria; Maximianus Ardon Bidi,; Veronika Ina Assan Boro, (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The socialization activity on increasing public awareness of women's rights in village development participation was carried out in Jawapogo Village, Mauponggo District, Nagekeo Regency. This activity aims to encourage changes in the community's mindset towards the strategic role of women in fair and inclusive village development. Through an educational approach, this activity targets mothers and young women as key groups in the process of strengthening capacity and understanding of gender equality and women's rights. The results of the activity showed an increase in participants' understanding of the concept of gender equality, courage in voicing opinions in public spaces, and a growing enthusiasm to be actively involved in village development activities. This socialization proves that a participation-based approach and critical awareness can be an effective strategy in increasing women's involvement at the village level, while encouraging the creation of a more just, equal, and sustainable society. Keywords: Awareness, Women, Participation, Development, Right